La mujer sin cabeza [videorecording (DVD)] = The headless woman - Martel, Lucrecia, 1966-; Onetto, María; Cantero, Claudia; Bordón, César, 1961-; Genoud, Daniel; Arengo, Guillermo (Strand Releasing Home Video, 2009)
A bourgeois woman is driving alone on a dirt road when she becomes distracted and runs over something. In the days following this jarring incident, she becomes dazed and emotionally disconnected from the people and events in her life. She becomes obsessed with the possibility that she may have killed someone. The police confirm that there were no accidents reported in the area and everything returns to normal. That is until a gruesome discovery is made.